2011
DOI: 10.1038/pr.2011.24
|View full text |Cite
|
Sign up to set email alerts
|

Variations in CRHR1 are associated with persistent pulmonary hypertension of the newborn

Abstract: Persistent pulmonary hypertension of the newborn (PPHN) is associated with substantial infant morbidity and mortality. Recently, genetic associations have been found in idiopathic pulmonary arterial hypertension. We performed a family-based candidate gene study to examine a genetic association to PPHN and sequenced the BMPR2 gene in 72 individuals. We enrolled 110 families with infants diagnosed with PPHN based on inclusion criteria. After medical chart review, 22 subjects were excluded based on predefined cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 49 publications
1
30
0
Order By: Relevance
“…Genetic variation in CRHR1 has also been associated with persistent pulmonary hypertension of the newborn suggesting a possible role with pulmonary disease in the newborn. 20 Prior studies also suggest a role for the corticotrophin releasing hormone system regulation of birthweight and SGA which we again identified in our study. 21,22,23 …”
Section: Discussionsupporting
confidence: 86%
“…Genetic variation in CRHR1 has also been associated with persistent pulmonary hypertension of the newborn suggesting a possible role with pulmonary disease in the newborn. 20 Prior studies also suggest a role for the corticotrophin releasing hormone system regulation of birthweight and SGA which we again identified in our study. 21,22,23 …”
Section: Discussionsupporting
confidence: 86%
“…In a Dutch cohort with excellent early ascertainment, PPHN was documented in 5.2% of Down syndrome infants [15] and other studies have shown that Down syndrome infants are overrepresented in neonates requiring ECMO support [16]. A recent single-center study reported the results of rigorous genotype analysis of 88 neonates with documented PPHN [17]. No differences were noted in most candidate genes, including BMPR2 and nitric oxide (NO) synthase.…”
Section: Classification Epidemiology and Pathogenesis Of Pphnmentioning
confidence: 98%
“…Recent identification of genetic variations involving corticotropin-releasing hormone in patients with PPHN, as well as the effectiveness of hydrocortisone in improving oxygenation in lambs with PPHN, suggest that glucocorticoids may have a role in prevention and management of PPHN and HRF. 37,38 …”
Section: Transition At Birthmentioning
confidence: 99%